Faktor Risiko Kejadian Stunting pada Anak Usia di bawah 2 Tahun: Studi Cross-Sectional di Pulau Jawa-Indonesia dengan menggunakan Data Studi Status Gizi Indonesia Tahun 2021: Faktor Risiko Stunting pada Baduta di Pulau Jawa: Studi Cross-Sectional Menggunakan Data Studi Status Gizi Indonesia Tahun 2021 - Paramita, Muthia; Helmyati, Siti; Basrowi, Ray Wagiu; Dilantika, Charisma (Universitas Airlangga, 2023)
Background: Stunting is a malnutrition problem that requires attention, with a prevalence of 24.4% in 2021. As the most populous island in Indonesia, Java Island has a significant impact on the incidence of stunting. Objectives: This study aims to determine the prevalence of stunting in infants and to identify factors associated with the incidence of stunting in each province of Java. Methods: This study used secondary data from the Indonesian Nutrition Status Study (INSS) conducted in 2021 with a cross-sectional design. A logistic regression test with weighting was conducted to determine the relationship between each variable and the incidence of stunting. Results: The prevalence of stunting in infants was measured in several regions of Indonesia, including DKI Jakarta (11.9%), West Java (16.3%), Central Java (13.2%), DI Yogyakarta (12.1%), East Java (15.9%), and Banten (14.6%). Risk factors for stunting were identified in DKI Jakarta, namely economic status in quintile 1 (p = 0.001), and in West Java, namely snack consumption (p = 0.002) and economic status in quintile 1 (p < 0.001). In Central Java, the risk factor was economic in quintile 1 (p = 0.048), while in the Special Region of Yogyakarta, it was age 12-23 months (p = 0.022). In East Java, infants aged 9-11 months (p = 0.013) and 12-23 months (p < 0.001) with low (p = 0.010) and middle (p = 0.017) mother's education level and economic status in quintile 1 (p = 0.005) were found to be at risk. In Banten were male infants (p = 0.011) in rural areas (p = 0.039) and with economic status in quintile 1 (p = 0.019) were found to be at risk. Conclusions: Economic status is a risk factor for stunting on Java Island. Interventions can be targeted towards improving economic status.